2005
DOI: 10.1097/01.olq.0000175391.13947.f7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gender and Sex Work on Sexual and Injecting Risk Behaviors and Their Association With HIV Positivity Among Injecting Drug Users in an HIV Epidemic in Togliatti City, Russian Federation

Abstract: IDUs involved in sex work and IDU nonSWs require specific and targeted interventions to facilitate safer injecting and sexual behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 35 publications
2
51
0
Order By: Relevance
“…4 Studies in Russia and Bangladesh, among other places, have shown that IDU sex workers are more likely than nonsex worker IDUs to engage in risky injecting practices. 34,35 In China, compared to non-IDU sex workers, IDU sex workers have more clients, use condoms less often and are more likely to share syringes. 13,30 The greater likelihood that IDU sex workers will be street-based may also increase the likelihood that they will have IDU clients, and evidence from many regions of IDUs' inconsistent condom use 16,17,[36][37][38][39] suggests that this is a particularly high risk activity.…”
Section: Transactional Sex and Commercial Sex Workmentioning
confidence: 99%
“…4 Studies in Russia and Bangladesh, among other places, have shown that IDU sex workers are more likely than nonsex worker IDUs to engage in risky injecting practices. 34,35 In China, compared to non-IDU sex workers, IDU sex workers have more clients, use condoms less often and are more likely to share syringes. 13,30 The greater likelihood that IDU sex workers will be street-based may also increase the likelihood that they will have IDU clients, and evidence from many regions of IDUs' inconsistent condom use 16,17,[36][37][38][39] suggests that this is a particularly high risk activity.…”
Section: Transactional Sex and Commercial Sex Workmentioning
confidence: 99%
“…In summary, current research indicates that IDUs and risky drinkers in Russia are experiencing notable rates of HIV/STI and report notable HIV risks, including multiple partners, sex trade involvement and unprotected sex (Benotsch et al 2004;Krupitsky et al 2004;Platt et al 2005;Rhodes et al 2004;Somlai et al 2002;Takacs et al 2006;Karapetyan et al 2002). Such research has not, however, examined associations between HIV/STI risk histories and condom use.…”
Section: Sexual Transmission Of Hiv Infection Within Russia Is Assumementioning
confidence: 93%
“…The epidemic has been propelled even further via the link between injection drug use and sex work, particularly for female IDUs. A substantial proportion of female IDUs (37%) report having engaged in sex work (Benotsch et al 2004), and those engaging in sex work are more likely to report both risky injection drug use and a history of sexually transmitted infections (STIs), as compared with male IDUs or female IDUs reporting no history of sex work (Karapetyan et al 2002;Platt et al 2005). Nonetheless, awareness of HIV risk among IDUs is increasing (UNAIDS 2006b), and HIV risk perceptions among IDUs in Russia are actually greater than that seen in the United States (US) (Ksobiech et al 2005).…”
Section: Sexual Transmission Of Hiv Infection Within Russia Is Assumementioning
confidence: 99%
“…For example, in Tijuana and Ciudad Juarez, Mexico, HIV prevalence among IDU-FSWs was more than twice that of FSWs who did not inject drugs (12% versus 5%) . The IDU-FSWs tended to show higher rates of borrowing injection equipment, practicing needle or syringe sharing (possibly with multiple sex partners), injecting with a needle/syringe previously used by someone known to be HIV/HCV positive, overdosing, and injecting on a daily basis (Platt et al, 2005;Gu et al, 2008;Weber et al, 2002;Spittal et al, 2003). IDU-FSWs often shared needles with their IDU clients if the clients sent them to procure drugs and the needles to use, therefore borrowing and lending equipment was often a part of the sex trade (Spittal et al, 2003;Spittal et al, 2001).…”
Section: Synergetic Effect Between the Sex Trade And Drug Usementioning
confidence: 99%
“…Injection drug use was inextricably linked to commercial sex (Tyndall et al, 2002). For example, in various locations in the Russian Federation, between 15% and 66% of female IDUs were involved in sex work (Platt et al, 2005;Dehne & Kobyshcha, 2000); over half of female IDUs in China (52-98%) were involved in sex work (Yang et al, 2005;Gu et al, 2008); and two-thirds of female drug users in Manipur, India, reported exchanging sex for money or drugs (Panda et al, 2001). …”
mentioning
confidence: 99%